PROFILE OF STUDENT'S MATHEMATICAL PROBLEM SOLVING ABILITY BASED ON LINGUISTIC INTELLIGENCE AND MATHEMATICAL LOGICAL INTELLIGENCE - Hestu Wilujeng; Edi Irawan; Prahesti Tirta Safitri; Aan Subhan Pamungkas (Prima: Jurnal Pendidikan Matematika, 2021)
The process of solving problems carried out by students in stages, namely understanding problems, planning solutions, carrying out solutions and checking again. Solving student problems varies according to the basic characteristics of students' interests, talents and potential. Learning will be more optimal if it is adjusted to the intelligence possessed by students. The goal is that teachers can facilitate learning according to the intelligence possessed by students, so the teacher must know the intelligence possessed by students. This research is a qualitative study using two subjects, namely the subject of linguistics and the subject of mathematical logic. The results showed that at the problem-understanding stage, SLM completed using formulas, completed according to plan and checked by recalculating. SL uses more trial-and-error reasoning, understanding information by reading sentences quickly as well as checking again.